PRODUCTION DEVELOPMENT AND MAIZE CONSUMPTION IN NORTH SUMATRA PROVINCE - Gustina Siregar; Saleh Nugraha (JASc (Journal of Agribusiness Sciences), 2017)
The state of Indonesia is an agrarian country, most of its livelihoods are farming. In Indonesia, corn is one of the food ingredients that the government recommends because it sees the huge need of rice. The government made efforts to realize the self-sufficiency of corn production in North Sumatra Province. For that Prediction of corn production development is needed to know the expected target is achieved. Corn production prediction is done using linear trend line formula and data taken in the form of corn production data from 2005 until 2015. North corn maize production until 2015 continues to experience enhancement. Total corn production is 12,369,482 tons, and total corn consumption until 2015 is 690.363 tons. There was a surplus of 10,679,119 tons. Based on the prediction result until 2020 maize production is 8,382,273 tons and corn consumption is 344,990 tons, so the surplus is 8,037,283 tons. This surplus occurs because the corn demand for the industry has not been taken into account.Keyword : Prediction, Maize Production, Linear Trend Line